DNA-damaging chemical agents: genotoxicity induction in daily life, risk and prevention - Montero-Campos, Virginia (2024)
Genotoxic agents are substances that can induce DNA damage; this damage can be caused by chemical, biological, and physical agents. The dose, time and route of exposure, and the genetic constitution of the individual influence the capacity of these agents to induce damage and may also be related to lifestyle habits and place of residency. Directly associated with genotoxicity is epigenetics, which is the study of hereditary changes in the function of hereditary genes not attributed to alterations in the DNA sequence. These processes regulate the expression of genes through the modulation of chromatin structure. The interaction of genetic and non-genetic factors in the control of hereditary patterns of this expression may cause diseases or disorders such as cancer, infertility, inflammatory processes, degenerative diseases, and endocrine disruption that could be transmitted to the offspring. Several epidemiological studies have shown that changes in lifestyle and eating habits could prevent or reduce cancer incidence; particularly by increasing the level of antioxidants and reducing the formation of free radicals with intracellular effects. At the Biotechnology Research Center of the Technological Institute of Costa Rica, various genotoxic agents to which the population in Costa Rica is exposed are investigated, including bacteria such as Helicobacter pylori, micro plastics in marine species for human consumption, and heavy metals in drinking water and in soils. These investigations are relevant to determine the presence of these genotoxic agents in the country, to evaluate the risk of exposure of the population, and thus generate strategies for prevention and mitigation of the damage.